Application of a Bacterial Artificial Chromosome Modification System for a Human Artificial Chromosome Vector - Yamaguchi, Shigeyuki (Tottori University Faculty of Medicine, 2011)
Exactly controlled conditional gene expressing systems are crucial for genomic functional research, animal transgenesis and gene therapy. Bacterial artificial chromosomes (BACs) are optimal for harboring long fragments of genomic DNA or large cDNA up to 300 kb in size. Therefore, BACs are available to produce transgenic cells and animals for the functional studies of genes. However, BAC can insert DNA randomly into the host genome, possibly causing unpredicted expression. We previously developed a human artiﬁcial chromosome (HAC) vector from human chromosome 21 using chromosome engineering. The HAC vector has several important characteristics desired for an ideal gene delivery vector, including stable episomal maintenance, and the ability to carry large genomic DNA containing its own regulatory element, thus allowing physiological regulation of the transgene in a manner similar to that of the native chromosome. In this study, we develop a system fusing BAC library and HAC technology together to allow tight control of gene expression. This system enables BAC to be cloned into the defined locus on the HAC vector by the Cre/loxP system. In addition, the genome in the BAC is possible to be engineered freely by the BAC recombineering technology. This system is a highly efficient tool for the rapid generation of stringently controlled gene expression system on the HAC vector.